Development of filtering system for the production of biodiesel from used cooking oil - Noor Adilah, Md Arifin (2006)
Biodiesel can be produced from many sources such as rapeseed oil, vegetable oil, used cooking oil and many more. From the point of view price and available capacity used cooking oils (UCO) represent an attractive raw material for the production of methyl esters (ME) known as biodiesel as alternative fuels for diesel engines. The purpose of this study is to develop a filtering system to get a cleaner used cooking oil to produce biodiesel, beside that to study the effect of the base catalyst in producing biodiesel from filtered used cooking oil. The filter is built from polypropylene filter beg, PVC vessel and the base made from wood. Determination of the filtering system effectiveness and the effect of the catalyst is by using gas chromatography (GC) to detect the presence of methyl palmitate that is one of the component in methyl ester. From this result of the experiment the filtering system that had been fabricate can be used to treat the UCO and the exactly amount of catalyst needed is 1.00gram for the react with 250mL UCO and 50mL MeOH.